PENGARUH LATIHAN JAVELIN THROWERS EXERCISE TERHADAP KEKUATAN OTOT LENGAN DAN BAHU MAHASISWA KEPELATIHAN TAHUN AJARAN 2015/2016 - M. Fachmi M. Fachmi; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on the results of interviews of researchers with lecturers athletic courses, namely Mrs. Ni Putu Nita Wijayanti, M. Pd, obtained information that the ability of student javelin throwing is still less than the maximum. This is due to the lack of power at the time of throwing, so that the throw is not maximal or does not meet the target. This research aims to determine the significant effect of Javelin Thrower exercise, Exercise on muscle strength of arms and shoulders of 2015/2016 school year coach students. In this research the population to be used is the students of coaching semester 3B academic year 2015/2016 University of Riau, which amounted to 30 people. The sampling technique to be used is full sampling, ie the sample sampling when all members of the population are used as a sample, so that the sample amounted to 30 people. The research instrument used is the strength of arm and shoulder test with Expanding Dynamometer. The results obtained in the analysis using the t-test. The t test analysis yielded t count of 2.304 with ttable 1,699 then H_a rejected, at alfa (α) 0,05 level. It can be concluded that there is an effect of javelin thrower exercise, exercise of muscular strength of arm and shoulder In Student Putra Kepelatihan Force 2015/2016.Keywords : Javelin Thrower, S Exercise, Muscle Arm and Shoulder Strength